Case-based teaching using the Laboratory Animal System for learning C/C++ programming - Tan, Jun; Guo, Xianping; Zheng, Weishi; zhong, Ming (Computers and education, 2014)
Teachers and students often consider learning programming a difficult pursuit. Face-to-face learning alone cannot provide effective teaching or efficient solutions for learning. A case teaching model can make students active in programming courses, even as it relies on solid learning theory and pedagogical strategies. This paper reports a study based on a case teaching model in C/C++ programming. The Laboratory Animal System (LAS) is a standalone case for management of laboratory animals. This paper includes an overview of LAS architectural design and user interface by C/C++ and presents the design, implementation, and evaluation of the model, as well as its implications for learning computer programming. The case method provides an interactive learning environment for students. Based on a survey of student feedback, students can learn C/C++ programming and gain knowledge more quickly and effectively using the case teaching model than through some traditional methods of teaching. •Apply our approach for case teaching to C/C++ programming.•Illustrate the advantages of our method based on our experience with teaching C/C++.•Examine curriculum design and train student capability in programming.